Perceptions of Venezuelan migration: causes, Spain as a destination, return expectations - Castillo Crasto, Tomás; Reguant Álvarez, Mercedes (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2017)
Venezuela, throughout its history has been a host country for immigrants. Currently, it presents a completely different migration pattern, motivated by a national crisis in a context of institutional deterioration, economic recession and social breakdown, a situation that has worsened over the past 17 years. This work is an exploratory study of qualitative orientation. It done through a literature review of secondary sources and in-depth consultation Venezuelan immigrants, who offer their insight into five dimensions: migration path, education, training and employment status, participation in networks, Venezuelan socioeconomic status and return expectations. The main findings, both documentary sources and empirical inquiry, remind us of the existence of a serious deterioration in the current living conditions in the country and the need for a profound change in the political, economic and social level as a prerequisite for a possible return.
Keywords: international migration; perception; return; political situation and socioeconomic